A Case-Control Study on the p73 G4A Gene Polymorphism and Susceptibility to Breast Cancer in an Iranian Population - Zeinab TAVAKKOL AFSHARI; Zahra GHOLIZADEH; Amin Reza NIKPOOR; Jalil TAVAKKOL AFSHARI; Rashin GANJALI; Fatemeh HOMAEI SHANDIZ; Khadijeh JAMIALAHMADI (Tehran University of Medical Sciences, 2019)
Background: The tumor protein p73 (TP73) is a homolog of TP53 family. Ectopic p73 overexpression largely mimics p53 activities as a tumor suppressor and activates the transcription of p53-responsive genes and as a result induce apoptosis. This study aimed to investigate the association between p73 G4A polymorphism and the risk of breast cancer in a northeastern Iranian population. Methods: This case-control study was performed on 105 patients who admitted in educational hospitals of Mashhad University of Medical Sciences, Iran during 2013-2015, with breast cancer as case group and 120 healthy women as the control group. PCR-CTPP method was used to investigate the relationship between the p73 G4A polymorphism and the risk of breast cancer. Results: There was no significant association between the AA genotype of the p73 G4A polymorphism and breast cancer in case and control groups. Although G allele frequency was higher in the case group, the abundance of this allele between case and control groups was not statistically meaningful and, as a result, not associated with the risk of breast cancer in this study group. Conclusion: There was no association between G4A p73 polymorphism and the risk of breast cancer in a northeastern Iranian population.